Peran Prodi Manajemen Dakwah untuk Memperkuat Profesi Pengelola Zakat: Studi Kasus di Lembaga Amil Zakat - Kahfi, Al; Fadilah, Nurul (Idarotuna, 2024)
This study aims to explore the opportunities for the profession of zakat management in Indonesia and emphasizes the role of students of da'wah management in increasing the effectiveness of zakat management. The method used is field and library research by combining empirical data from the field with existing theories and literature. The findings of this study indicate that professional and organized zakat management is very much needed to support the optimization of zakat in empowering the people's economy. In addition, this finding also confirms that students majoring in da'wah management have a strategic role in managing zakat in the future. Through proper education, application of technology, and effective collaboration, students of Da'wah Management can contribute significantly to optimizing zakat management. Therefore, it is necessary to optimize collaboration between zakat management institutions and professionals, especially Da'wah Management students, who have a good understanding of sharia and zakat management.